2013
DOI: 10.1503/jpn.110188
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of the left hemispheric emotional attention neural network in risk for and protection from depression

Abstract: IntroductionIndividuals with a first-degree relative who has major depressive disorder (MDD) are at a 2-to 3-fold greater risk for depression than those without a family history of MDD. 1 Rela tives of depressed patients, compared with individuals without family history of psychiatric disorders, are characterized by elevated neuroticism, depressive cognitions and rigidity 2 and by stability of these traits over time.3 Patients with MDD who had relatives with an affective disorder display greater neuroticism 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 77 publications
(154 reference statements)
4
26
0
Order By: Relevance
“…In contrast, altered signalling in the supramarginal gyrus in familial risk for MDD as observed in our PPI analyses matches a previous report on functional alterations in familial risk 12 and might again point to altered executive functioning in individuals at risk for MDD, whereas the relevance of enhanced task-specific coupling between the OFC and the occipital cortex remains uncertain so far owing to lacking corresponding evidence from the literature. In a more general sense, the present results highlight the urgent need for a more detailed understanding of aberrant network signalling in MDD.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In contrast, altered signalling in the supramarginal gyrus in familial risk for MDD as observed in our PPI analyses matches a previous report on functional alterations in familial risk 12 and might again point to altered executive functioning in individuals at risk for MDD, whereas the relevance of enhanced task-specific coupling between the OFC and the occipital cortex remains uncertain so far owing to lacking corresponding evidence from the literature. In a more general sense, the present results highlight the urgent need for a more detailed understanding of aberrant network signalling in MDD.…”
Section: Discussionsupporting
confidence: 88%
“…Out of the few studies available, DLPFC hypoactivation was reported in individuals at familial risk during presentation of fearful faces, 8 highly matching the present results, but also during an automatic mood regulation paradigm. 38 Moreover, Lisiecka and colleagues 12 showed aberrant functioning in further brain areas thought to be of high relevance for execu tive control during emotional processing, including the inferior parietal gyrus and the postcentral gyrus in unaffected first-degree relatives of patients with MDD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, people at familial risk of depression do overactivate subcortical, affectlinked, areas in a task requiring the shifting of attention from negative stimuli. This has been attributed to a compensatory 'protective' strategy in at-risk individuals (Lisiecka et al 2013), and it is possible that a similar effect could underlie the changes seen in our study.…”
Section: Discussionsupporting
confidence: 64%
“…Such a system could assist the doctors to take decisions in much-needed situations. Danuta [10], stated that family history of MDD increases individuals' vulnerability to depression and alters the way depression manifests itself. Emotion processing and attention shifting are functions altered by MDD and family history of the disease; therefore, it was important to recognize the neural correlates of these functions in association with both factors.…”
Section: Literature Surveymentioning
confidence: 99%